PUBLIC RELATION DAN REPUTASI YANG BERDAMPAK PADA LOYALITAS KONSUMEN DENGAN IMAGE SEBAGAI VARIABEL MEDIASI - Alfredy Donny Haposan Harianja; Irsal Fauzi; Abdul Aziz (Jibaku: Jurnal Ilmiah Bisnis, Manajemen dan Akuntansi, 2021)
Business competition is getting tougher in the era of globalization today make it every company is required to be able to compete and set the right marketing strategy. Marketing aims to build and retain customers who can benefit the company. The existence of trust from the public (public trust) will provide a positive image of the company's existence and have an impact on the loyalty of consumers who use the company's services and products. This study aims to determine the effect of public relations and reputation mediated by image which has an impact on loyalty. The method used is inferential analysis (quantitative) with multiple regression analysis techniques and for the sample obtained a sample of 100 respondents with a purposive sampling technique. the results of simultaneous analysis of public relations and reputation mediated by image have a significant effect on loyalty. To maintain customer loyalty in the future, company should be more aggressively in building public relations and company reputation, so company's image among consumers can be better.